2016
DOI: 10.1111/liv.13207
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of controlled attenuation parameter for the noninvasive assessment of liver steatosis

Abstract: In patients with chronic viral hepatitis and advanced liver fibrosis, controlled attenuation parameter performs better than ultrasound for assessing liver steatosis, whereas in patients without viral hepatitis and with nonsignificant liver disease ultrasound shows the best performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…This study confirmed the diagnostic value of the CAP for the detection of steatosis compared with US as a reference method in the general population as previous studies have demonstrated in patients with chronic liver diseases [24]. Recently, an Italian study compared the use of CAP and US in a cohort predominantly affected by chronic viral hepatitis [25]. This study demonstrated that, in patients with chronic viral hepatitis, CAP was superior to US in detecting hepatic steatosis, whereas in patients with nonsignificant liver disease, US performed better than CAP.…”
Section: Introductionsupporting
confidence: 86%
“…This study confirmed the diagnostic value of the CAP for the detection of steatosis compared with US as a reference method in the general population as previous studies have demonstrated in patients with chronic liver diseases [24]. Recently, an Italian study compared the use of CAP and US in a cohort predominantly affected by chronic viral hepatitis [25]. This study demonstrated that, in patients with chronic viral hepatitis, CAP was superior to US in detecting hepatic steatosis, whereas in patients with nonsignificant liver disease, US performed better than CAP.…”
Section: Introductionsupporting
confidence: 86%
“…Therefore we fitted two-level Bayesian latent class models with discrete latent variables to estimate sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of diagnostic tests (imperfect gold standard methodology), as previously reported [14]. Briefly, the observed results of the diagnostic tests are considered as a measure, prone to error, of an unobservable (latent) dichotomous variable, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Abdominal gas or obesity may decrease the applicability of B-mode US. Moreover, in patients with liver fibrosis the accuracy of the technique for diagnosing hepatic steatosis may decrease[8,9]. On the other hand, a significant intra- and inter-observer variability for the assessment of the US findings of liver steatosis has been reported[10,11].…”
Section: Ultrasound: Semiquantitative Assessmentmentioning
confidence: 99%